Mixed department (Stereometry) (Texas Journal of Multidisciplinary Studies, 2023)
This article describes in detail the transformative potential of modern technologies, the axioms of stereometry, and the results derived from the axioms of stereometry, with special attention to virtual reality in the context of teaching stereometry.